Analisis Kemampuan Representasi Matematis Siswa SMP Kelas VIII pada Materi Persamaan Garis Lurus - Dwiyacob, Linjanie; Aini, Indrie Noor (Program Studi Sarjana Pendidikan Matematika, Universitas Singaperbangsa Karawang, 2023)
Students' mathematical representation ability is a cognitive ability that is very important and needed by every student to solve mathematical problems. The purpose of the research conducted was to determine the level of representation ability of junior high school students in grade VIII. In the study, researchers used descriptive research methods along with a qualitative approach. The main instrument in the research is the researcher himself and is supported by a mathematical representation ability test instrument containing 3 questions with straight line equation material. The data collection technique that researchers use is a test instrument for all students. The results of the study found that (1) students' visual representation ability in the form of graphs on straight line equation material obtained a percentage of 63.67%; (2) representation ability in the form of mathematical equations obtained a percentage of 53.33%; (3) written text verbal representation ability obtained a percentage of 46.11%; (4) overall students' mathematical representation ability is included in the moderate category. It can be concluded that the overall mathematical representation ability of class VIII students is in the moderate category seen from the three indicators that have not been fulfilled.